Community Engagement Program for School Teacher Groups Using SiPETA to Support Children with Learning Difficulties in Depok, West Java - Suzy Yusna Dewi; Netti Herawati; Taufiq Fredrik Pasiak; Melly Kristanti; Yaya Aria Santosa; Yasmin Azizah Idhsa (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2026)
Human resource development is a primary focus of the 2020–2024 National Medium-Term Development Plan (RPJMN), which emphasizes the importance of quality education from an early age. In Depok City, educational inequality and low achievement in the Programme for International Student Assessment (PISA) in reading and critical thinking indicate the need for targeted intervention. This community service program aims to improve the competence of elementary school teachers in supporting students with learning difficulties through the utilization of SiPETA (Sistem Pelatihan Otak), a digital brain-training application designed based on Bloom’s Taxonomy to enhance reading skills, attention, memory, self-regulation, and critical thinking. The program was implemented through structured training for elementary school teachers, who subsequently applied SiPETA to students with learning difficulties. The activities included guided training, classroom implementation, and evaluations conducted in the first and third months. The results showed an improvement in teacher competence, with efficacy scores increasing by 31% and knowledge scores by 40%. This program strengthens teacher capacity and supports the achievement of Sustainable Development Goal (SDG) 4: Quality Education.